If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6) + 3y = 18 Multiply 4 * 6 24 + 3y = 18 Solving 24 + 3y = 18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 3y = 18 + -24 Combine like terms: 24 + -24 = 0 0 + 3y = 18 + -24 3y = 18 + -24 Combine like terms: 18 + -24 = -6 3y = -6 Divide each side by '3'. y = -2 Simplifying y = -2
| lnx=-7 | | X^4=8x^2+20 | | 16x+1+25=122 | | b(13b+5)=8 | | x+4-6=2x-6 | | 16x+26=122 | | 8x=9x-5/2 | | x^2=6x+4 | | 3.67+3= | | -4x^2+24x=0 | | (X-3)+x+((x-3)*3)=38 | | 9b-2=-38 | | 15n-4=41 | | 7n+2=9 | | -(1/3)-(2/3)=x | | -3v-3x=15 | | -3v+3x=12 | | 1m+5=25+4 | | -5a+c=-30 | | 101-6x=12x+19 | | ln(8x+5)=ln(5x-1) | | -2/3*i=-3 | | 2y-6z=-12 | | 16x=9x-5 | | 8h^4-26h^2+15=0 | | 4y/3=34 | | -2/3i=-3 | | 6a-2v=18 | | (7/8)*2+5y | | ln(4x-10)=ln(2x+4) | | (7/8)2+5y | | 2x^2-41x=-7x^2-6x-24 |